1997
DOI: 10.1063/1.872103
|View full text |Cite
|
Sign up to set email alerts
|

A study of picosecond laser–solid interactions up to 1019 W cm−2

Abstract: The interaction of a 1053 nm picosecond laser pulse with a solid target has been studied for focused intensities of up to 10 19 W cm Ϫ2. The maximum ion energy cutoff E max ͑which is related to the hot electron temperature͒ is in the range 1.0-12.0 MeV and is shown to scale as E max ϷI 1/3. The hot electron temperatures were in the range 70-400 keV for intensities up to 5ϫ10 18 W cm Ϫ2 with an indication of a high absorption of laser energy. Measurements of x-ray/␥-ray bremsstrahlung emission suggest the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
364
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(403 citation statements)
references
References 57 publications
(49 reference statements)
33
364
1
Order By: Relevance
“…Since the fast electron energy is dependent on I 0 k 2 0 , 31,32 it is possible using 3x radiation to obtain fast electrons with a range comparable to the size of the compressed target. The initial temperature and resistivity of the target are assumed to be 300 eV and 3 Â 10 À8 Xm.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Since the fast electron energy is dependent on I 0 k 2 0 , 31,32 it is possible using 3x radiation to obtain fast electrons with a range comparable to the size of the compressed target. The initial temperature and resistivity of the target are assumed to be 300 eV and 3 Â 10 À8 Xm.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In experiments at laser intensities up to 5 ϫ 10 18 W / cm 2 , Beg et al 19 used a combination of PIN diodes and scintillators to determine the bremsstrahlung spectrum in five spectral windows ranging up to 250 keV and found that the emission spectrum could not be fitted by a single temperature. Multichannel bremsstrahlung dosimeters based on thermoluminescence detectors or imaging plate detectors have been employed in intense laser-matter interaction experiments to determine the hot electron spectrum and the absolute conversion of laser energy into hot electrons.…”
Section: A Hot Electron Spectramentioning
confidence: 99%
“…Also plotted are 3 estimations of the hot electron temperature from Beg, Haines and Wilks [12][13][14]. Figure 3 b) clearly shows that the escaping hot electron temperature is very similar as the laser is defocussed over 3 orders of magnitude of incident intensity.…”
Section: Fig 2 Polar Plots Of the Angularly-resolved Electron Variedmentioning
confidence: 87%